On some properties of Schwartz–Gopengauz operator - Kirjackis, Eduardas (Lietuvos matematikos rinkinys, 2023)
The generalization of Schwarz’s derivative proposed by B.E. Gopengauz, which is applied to the study of the properties of the class of functions with nonvanishing in the unit circle divided difference of n-th order is examined.
Keywords: holomorphic function; operator; functional; divided difference